Transfusion therapy of neonatal and paediatric patients: They are not just little adults. Issue 6 (7th October 2022) - Gammon, Richard R.; Al‐Mozain, Nour; Auron, Moises; Bocquet, Christopher; Clem, Sam; Gupta, Gaurav K.; Hensch, Lisa; Klein, Norma; Lea, Nicole C.; Mandal, Saikat; Pelletier, Peter; Resheidat, Ashraf; et al.
Abstract: Patient blood management (PBM) strategies are needed in the neonate and paediatric population, given that haemoglobin thresholds used are often higher than recommended by evidence, with exposure of children to potential complications without meaningful benefit. A literature review was performed on the following topics: evidence‐based transfusions of blood components and pharmaceutical agents. Other topics reviewed included perioperative coagulation assessment and perioperative PBM. The Transfusion and Anaemia Expertise Initiative (TAXI) consortium published a consensus statement addressing haemoglobin (Hb) transfusion threshold in multiple subsets of patients. A multicentre trial (PlaNeT‐2) reported a higher risk of bleeding and death or serious new bleeding among infants who received platelet transfusion at a higher (50 000/μl) compared to a lower (25 000/μl) threshold. Recent data support the use of a restrictive transfusion threshold of 25 000/μl for prophylactic platelet transfusions in preterm neonates. The TAXI‐CAB consortium mentioned that in critically ill paediatric patients undergoing invasive procedures outside of the operating room, platelet transfusion might be considered when the platelet count is less than or equal to 20 000/μl and there is no benefit of platelet transfusion when the platelet count is more than 50 000/μl. There are limited controlled studies in paediatric and neonatal population regarding plasma transfusion. Blood conservation strategies to minimise allogenic blood exposure are essential to positive patient outcomes neonatal and paediatric transfusion practices have changed significantly in recent years since randomised controlled trials were published to guide practice. Additional studies are needed in order to provide practice change recommendations.